1999
DOI: 10.1159/000054072
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Micronized Purified Flavonoid Fraction: An Overview

Abstract: Flavonoids are widely used for the treatment of chronic venous insufficiency (CVI). In clinical trials, micronized purified flavonoid fraction (MPFF, 450 mg diosmin plus 50 mg hesperidin, Daflon 500 mg) has demonstrated its activity in CVI by improving venous tone and vein elasticity assessed by plethysmography. Randomized, double-blind, placebo-controlled clinical studies have shown an improvement in signs and symptoms related to CVI and a decrease in leg circumferences at the levels of the ankle and calf. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Despite the uncertainty, there are suggestions that tissue hypoxia may contribute to the remodelling seen in the varicose vein wall, and further investigation seems worthwhile. Furthermore, improving venous oxygenation, for example using flavonoids, may lead to symptomatic relief in CVI [17,19,66,67]. Interestingly, these drugs have been shown to improve venous oxygenation most likely by elevating venous tone, increasing ATP production, reducing vein wall inflammation and decreasing capillary permeability [35,64,66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the uncertainty, there are suggestions that tissue hypoxia may contribute to the remodelling seen in the varicose vein wall, and further investigation seems worthwhile. Furthermore, improving venous oxygenation, for example using flavonoids, may lead to symptomatic relief in CVI [17,19,66,67]. Interestingly, these drugs have been shown to improve venous oxygenation most likely by elevating venous tone, increasing ATP production, reducing vein wall inflammation and decreasing capillary permeability [35,64,66].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, improving venous oxygenation, for example using flavonoids, may lead to symptomatic relief in CVI [17,19,66,67]. Interestingly, these drugs have been shown to improve venous oxygenation most likely by elevating venous tone, increasing ATP production, reducing vein wall inflammation and decreasing capillary permeability [35,64,66]. Moreover, improving our understanding of the role of hypoxia in varicose vein formation may lead to the discovery of further therapeutic targets for drug development in this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micronised purifi ed fl avonoid fraction (MPFF), which consists of 90% micronised diosmin (a fl avone derivative) and 10% fl avonoids expressed as hesperidin (a fl avonone derivative), is an oral phlebotrophic drug which improves venous tone and elasticity and decreases venous distensibility and venous emptying times in patients with functional or organic chronic venous insuffi ciency (CVI) [6] . MPFF also improves lymphatic drainage in the advanced stage of CVI, reduces refl ux time of venous blood in patients with CVI and capillary hyperpermeability in patients suffering from idiopathic cyclic edema and symptomatic capillary fragility, and has antioxidant activities [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…MPFF also improves lymphatic drainage in the advanced stage of CVI, reduces refl ux time of venous blood in patients with CVI and capillary hyperpermeability in patients suffering from idiopathic cyclic edema and symptomatic capillary fragility, and has antioxidant activities [6][7][8] . It has an excellent safety profi le as documented by both toxicological animal studies and clinical studies, and has a tolerability profi le similar to that of placebo [6] . Most studies have shown that MPFF is an effective and well-tolerated drug in patients with chronic venous insuffi ciency.…”
Section: Introductionmentioning
confidence: 99%